2010
DOI: 10.1016/j.jmb.2010.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Mouse Elf3 C-terminal DNA-binding Domain in Complex with Type II TGF-β Receptor Promoter DNA

Abstract: The Ets family of transcription factors is composed of more than 30 members. One of its members, Elf3, is expressed in virtually all epithelial cells as well as in many tumors, including breast tumors. Several studies observed that the promoter of the type II TGF-β receptor gene (TβR-II) is strongly stimulated by Elf3 via two adjacent Elf3 binding sites, A-site and B-site. Here we report the 2.2 Å resolution crystal structure of a mouse Elf3 C-terminal fragment, containing the DNA-binding Ets domain, in comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 39 publications
(54 reference statements)
2
26
0
Order By: Relevance
“…The best known candidate is the gene encoding for TGF-b RII, as several studies have clearly shown that Elf3 can bind to the promoter and regulate transcription of the TGF-b RII gene. [27][28][29][37][38][39] Moreover, it has also been reported that Elf3À/À mice express reduced protein levels of TGF-b RII in the developing small intestinal epithelium when compared with Elf3 þ / þ mice. 26 Although TGF-b RII is a potent inhibitor of cell proliferation, it is very important for the induction of epithelial cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best known candidate is the gene encoding for TGF-b RII, as several studies have clearly shown that Elf3 can bind to the promoter and regulate transcription of the TGF-b RII gene. [27][28][29][37][38][39] Moreover, it has also been reported that Elf3À/À mice express reduced protein levels of TGF-b RII in the developing small intestinal epithelium when compared with Elf3 þ / þ mice. 26 Although TGF-b RII is a potent inhibitor of cell proliferation, it is very important for the induction of epithelial cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…26 Indeed, many in vitro studies have also established that the TGF-b RII gene is a definite target of Elf3, and that Elf3 transactivates the TGF-b RII gene promoter by binding to two adjacent ETS-binding sites. [27][28][29] Interestingly, ectopic expression of the human TGF-b RII transgene specifically in the intestinal epithelium of Elf3À/À mice can rescue the previously characterized intestinal defects of Elf3À/À mice. 30 This phenotypic rescue provides further in vivo evidence that Elf3 is the critical upstream regulator of TGF-b RII expression in the mouse small intestinal epithelium.…”
mentioning
confidence: 99%
“…30 Indeed, many in vitro studies have also established that the TGF-b RII gene is a definite target of Elf3, and that Elf3 transactivates the TGF-b RII gene promoter by binding to two adjacent ETS binding sites. [31][32][33][34][35][36][37] Interestingly, human gastric cancer cell lines do not express ESE-1 mRNA and in turn show undetectable levels of TGF-b RII mRNA. 38 Further evidence of ESE-1-mediating TGF-b RII gene expression has also been provided from experiments with human colon cancer cell lines.…”
Section: Ese-1 In Regulating Epithelial Cell Differentiation During Imentioning
confidence: 99%
“…34 In human colonic epithelial cells, ESE-1 has also been shown to regulate gene expression of the proinflammatory cytokine, macrophage inflammatory protein-3a (MIP-3a). 39 Another group has previously reported that CR6-interacting factor 1 (Crif1) plays an essential role in Elf3-mediated intestinal development by functioning as a transcriptional co-activator of Elf3 during terminal differentiation of the 25,30 Mouse bronchiolar airway epithelium 42 Mouse embryonal carcinoma cell line (F9) 33,35,37 Human embryonic kidney cell line (HEK 293T) 33,35,37 Human hepatoblastoma cell line (HepG2) 31 Human gastric cancer cell line (SNU-620) 31 Human colon cancer cell line (RKO) 34 Human breast cancer cell lines (SK-BR3, Hs578t) 31,32 Human cervical cancer cell line (HeLa 229) 31,33 Macrophage inflammatory protein-3a (MIP-3a)m Human colonic epithelial cell line (Caco-2) 39 Small proline-rich protein 1B (SPRR1B)m Primary human tracheobronchial epithelial cells 41 Human bronchial epithelial cell line (BEAS-2B) 41 Human lung adenocarcinoma epithelial cell line (NCI-H441) 41 Epithelium-specific ETS transcription factor-3 (ESE-3)m Human bronchial epithelial cell line (BEAS-2B) 44 Human lung carcinoma cell line (A549) 44 Interleukin-6 (IL-6)m Mouse lung tissue 44 Primary mouse airway epithelial cells 47 Primary mouse bone marrow-derived dendritic cells 47 Human bronchial epithelial cell line (BEAS-2B) 47 Interleukin-12 (IL-12)m Primary mouse bone marrow-derived dendritic cells 47 Lysozyme (LYZ)m Primary human bronchial airway epithelial cells 46 Human lung carcinoma cell line (A549) 46 Human lung mucoepidermoid carcinoma-derived cell line (NCI-H292) 46 Human lung adenocarcinoma epithelial cell line (NCI-H441) …”
Section: Ese-1 In Regulating Epithelial Cell Differentiation During Imentioning
confidence: 99%
“…Crystal structures of the ETS domains of several Ets transcription factors have been determined using X-ray crystallography and nuclear magnetic resonance techniques (Garvie et al, 2001;Kodandapani et al, 1996;Mo et al, 1998;Pufall et al, 2005;Wang et al, 2005;Lamber et al, 2008;Agarkar et al, 2010;Batchelor et al, 1998). A genome-wide analysis of Ets-family DNA binding in vitro and in vivo has recently been performed (Wei et al, 2010).…”
Section: Introductionmentioning
confidence: 99%